STUDENTS’ STRATEGIES IN COMPARING RATIONAL NUMBERS - Kurniati, Ratnah (International Conference on Cultural Studies, 2018)
There are many strategies in comparing rational numbers. Based on the observation, there was some students who used wrong strategies in comparing rational numbers. To fix this students problems, it was necessary to know that the original concept of them. So the objective of this research was to describe student’s strategies in comparing rational number. The results showed that in comparing rational number, students used same form strategy, students make the number in the same form and then compare it by used number line and also, other students used whole number thinking strategy.